Edible nanocomposite coating material imitating plant cuticle structure and preparation method and application thereof

CN122917601APending Publication Date: 2026-10-16ZHEJIANG UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611221593.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-12
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0003]现有技术中,淀粉基材料亲水性强、脆性大,现有单一增塑剂物理共混改性仅依赖氢键等弱相互作用,增塑剂易迁移析出,无法实现持久增韧;壳聚糖基材料机械强度低,纳米氧化锌等无机粒子简单物理共混易团聚,且壳聚糖仅在酸性条件下才能发挥抗菌活性,中性或微酸性环境下抗菌效果显著减弱;纳米纤维素表面羟基使其亲水性强、分散性差,现有疏水改性多为表面吸附或单一酯化处理,与成膜基体间缺乏化学键合,界面结合力弱,复合膜易相分离,且各功能组分之间多为物理共混或弱氢键结合,缺乏稳固的化学交联网络,整体结构松散,力学性能与阻隔性能难以协同提升

Benefits of technology

1、本发明中,改性淀粉基成膜材料经过氧化氢氧化引入羧基增加反应活性,经马来酸酐酯化引入双键提供交联位点,经三偏磷酸钠交联构建三维网状结构以提升膜强度,再经硬脂酰乳酸钠复合增塑在分子链间形成疏水微区并抑制增塑剂迁移,使淀粉膜从传统单一增塑物理共混的脆弱结构变为具有持久柔韧性和抗老化能力的稳定网络,解决了现有淀粉膜增塑剂易迁移析出、长期贮存性能劣化的问题,提升了膜的力学耐久性和阻水稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application relates to the technical field of food fresh-keeping materials, in particular to a biomimetic plant cuticle structure edible nano-composite coating material and a preparation method and application thereof, which comprises the following raw materials: modified starch-based film-forming material, modified chitosan-based reinforcing material and modified nano-cellulose-based hydrophobic material; in the application, the modified starch-based film-forming material has improved film-forming property, the film layer is flexible, continuous and free of cracking; the modified chitosan-based reinforcing material has enhanced mechanical strength and antibacterial activity, and can inhibit the breeding of pathogenic microorganisms on the surface of fruits and vegetables; the modified nano-cellulose-based hydrophobic material has improved hydrophobic barrier property, and epoxy groups are introduced on the surface as chemical crosslinking reaction active sites; after the three modified materials are compounded and flow-casted to form a film, the mechanical property, water and oxygen resistance and broad-spectrum long-acting antibacterial capacity are strong; when the material is used for fruit and vegetable preservation, water loss and quality deterioration can be delayed, and the shelf life is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of coal gangue dry slurry preparation technology, specifically to edible nanocomposite coating materials with a biomimetic plant cuticle structure, their preparation methods, and applications. Background Technology

[0002] The plant cuticle is a natural protective barrier covering the outer surface of epidermal cells of above-ground plant organs (such as leaves and fruits). It is mainly composed of cuticle polymers and embedded waxy components. After the edible film forms a protective layer on the surface of fresh fruits and vegetables, it can play a similar barrier role to the plant cuticle to a certain extent, slowing down water loss and gas exchange.

[0003] In existing technologies, starch-based materials are highly hydrophilic and brittle. Current physical blending modifications using single plasticizers rely solely on weak interactions such as hydrogen bonds, leading to easy migration and precipitation of the plasticizer, thus failing to achieve durable toughening. Chitosan-based materials have low mechanical strength, and simple physical blending of inorganic particles such as nano-zinc oxide easily results in agglomeration. Furthermore, chitosan only exhibits antibacterial activity under acidic conditions, with its antibacterial effect significantly weakened in neutral or slightly acidic environments. Nanocellulose's surface hydroxyl groups make it highly hydrophilic and poorly dispersible. Existing hydrophobic modifications are mostly surface adsorption or simple esterification treatments, lacking chemical bonding with the film-forming matrix, resulting in weak interfacial adhesion and easy phase separation of the composite film. Moreover, the functional components are mostly physically blended or weakly bonded, lacking a stable chemical cross-linking network, resulting in a loose overall structure and difficulty in synergistically improving mechanical and barrier properties. Based on this, this invention provides an edible nanocomposite coating material with a biomimetic plant cuticle structure, its preparation method, and its applications. Summary of the Invention

[0004] The purpose of this invention is to provide an edible nanocomposite coating material with a biomimetic plant cuticle structure, its preparation method, and its application. The edible nanocomposite coating material with a biomimetic plant cuticle structure prepared by this invention has a low plasticizer migration rate, indicating that the plasticizer has good adhesion to the membrane matrix and is not easily migrated or lost during long-term storage; the large diameter of the antibacterial zone indicates that the material dissolves more antibacterial active ingredients and has a strong antibacterial effect; the low water vapor permeability indicates that the membrane material has strong hydrophobic barrier properties and can effectively block external moisture penetration and internal moisture loss.

[0005] To achieve the above objectives, the present invention provides the following technical solution: an edible nanocomposite coating material with a biomimetic plant cuticle structure, composed of the following raw materials in parts by weight: 100 parts modified starch-based film-forming material, 20-30 parts modified chitosan-based reinforcing material, and 6-12 parts modified nanocellulose-based hydrophobic material.

[0006] The modified starch-based film-forming material is prepared by treating starch with hydrogen peroxide, maleic anhydride, sodium trimetaphosphate, and sodium stearoyl lactylate.

[0007] The modified chitosan-based reinforcing material is prepared by treating chitosan with acetic anhydride, epichlorohydrin, and nano-zinc oxide polyethylene glycol.

[0008] The modified nanocellulose-based hydrophobic material is prepared by treating nanocellulose with stearic acid, citric acid, and γ-glycidoxypropyltrimethoxysilane.

[0009] Further, the preparation method of the modified starch-based film-forming material is as follows: starch is dissolved in deionized water to prepare a starch slurry with a mass fraction of 10-20%, hydrogen peroxide is added, and the mixture is stirred at 40-60℃ to oxidize the starch to obtain oxidized starch; maleic anhydride is added to the oxidized starch, the pH is adjusted to 7.0-8.0, and the mixture is stirred at 50-70℃ to undergo an esterification reaction to obtain maleic anhydride esterified starch; sodium trimetaphosphate is added to the maleic anhydride esterified starch, the pH is adjusted to 9.0-10.0, and the mixture is stirred at 40-60℃ to undergo a crosslinking reaction to obtain crosslinked esterified oxidized starch; sodium stearoyl lactylate is added to the crosslinked esterified oxidized starch, and the mixture is stirred at 50-60℃ for composite plasticizing treatment, followed by filtration, washing, and drying to obtain the modified starch-based film-forming material.

[0010] Furthermore, the amount of hydrogen peroxide added is 3-5% of the dry weight of starch; the mass ratio of maleic anhydride to starch is 1:10-20; the mass ratio of sodium trimetaphosphate to starch is 1:30-40; and the mass ratio of sodium stearoyl lactylate to starch is 1:40-50.

[0011] Further, the preparation method of the modified chitosan-based reinforcing material is as follows: chitosan is dissolved in a 1% (w / w) aqueous acetic acid solution to prepare a 3-5% (w / w) chitosan solution; acetic anhydride is added, and the mixture is stirred at 40-60°C to undergo an esterification reaction to obtain esterified chitosan; epichlorohydrin is added to the esterified chitosan, and the mixture is stirred at 50-70°C to undergo a crosslinking reaction to obtain crosslinked esterified chitosan; nano zinc oxide is mixed with polyethylene glycol, dispersed in deionized water, ultrasonically dispersed, and then added to the crosslinked esterified chitosan; the mixture is stirred and compounded at 40-60°C, then filtered, washed, and dried to obtain the modified chitosan-based reinforcing material.

[0012] Further, the mass ratio of acetic anhydride to chitosan is 1:4-6; the mass ratio of epichlorohydrin to chitosan is 1:6-10; the nano zinc oxide and polyethylene glycol are mixed at a mass ratio of 1:2-4, the amount of nano zinc oxide added is 4-8% of the mass of chitosan, and the amount of polyethylene glycol added is 9-12% of the mass of chitosan.

[0013] Further, the preparation method of the modified nanocellulose-based hydrophobic material is as follows: nanocellulose is dispersed in deionized water to prepare a nanocellulose suspension with a mass fraction of 1-3%, stearic acid is added, and esterification reaction is carried out by stirring at 60-80℃ to obtain esterified nanocellulose; citric acid is added to the esterified nanocellulose, and crosslinking reaction is carried out by stirring at 70-90℃ to obtain crosslinked esterified nanocellulose; the crosslinked esterified nanocellulose is dispersed in an ethanol-water mixed solvent, γ-glycidoxypropyltrimethoxysilane is added, the pH is adjusted to 5.0-6.5, and coupling reaction is carried out by stirring at 50-70℃. After filtration, washing, and drying, the modified nanocellulose-based hydrophobic material is obtained.

[0014] Further, the mass ratio of stearic acid to nanocellulose is 1:3-5; the mass ratio of citric acid to nanocellulose is 1:6-10; the volume ratio of ethanol to water in the ethanol-water mixed solvent is 1:5-10; and the mass ratio of γ-glycidoxypropyltrimethoxysilane to nanocellulose is 1:15-25.

[0015] A method for preparing an edible nanocomposite coating material with a biomimetic plant cuticle structure includes the following steps: S1. Dissolve the modified starch-based film-forming material in deionized water to prepare a film-forming solution with a mass fraction of 4-6%, add a plasticizer, and gelatinize at 70-90℃; cool down to 40-60℃, add the modified chitosan-based reinforcing material, and stir to mix.

[0016] S2. Add modified nanocellulose-based hydrophobic material to the mixture obtained in S1, carry out ring-opening addition reaction to form chemical covalent crosslinking, and stir to disperse to obtain composite film-forming liquid.

[0017] S3. Vacuum degas the composite film-forming liquid for 10-20 minutes, and then cast it onto a flat substrate, controlling the casting thickness to be 0.5-2.0 mm.

[0018] S4. Dry the film cast in S3 at 40-60℃ to obtain an edible nanocomposite coating material with a biomimetic plant cuticle structure.

[0019] Furthermore, the plasticizer is glycerol, and the amount of glycerol added is 15-30% of the mass of the modified starch-based film-forming material.

[0020] Application of edible nanocomposite coating material with biomimetic plant cuticle structure: The edible nanocomposite coating material is prepared into a coating liquid with a mass fraction of 3-5%, sprayed onto the surface of fruits and vegetables, and dried with hot air at 30-40℃, thus forming an edible nanocomposite coating with biomimetic plant cuticle structure on the surface of fruits and vegetables.

[0021] Compared with the prior art, the beneficial effects of the present invention are: 1. In this invention, the modified starch-based film-forming material introduces carboxyl groups through oxidation and oxidation to increase reactivity, introduces double bonds through maleic anhydride esterification to provide crosslinking sites, constructs a three-dimensional network structure through sodium trimetaphosphate crosslinking to improve film strength, and then forms hydrophobic microregions between molecular chains and inhibits plasticizer migration through sodium stearoyl lactylate composite plasticizing. This transforms the starch film from a fragile structure of traditional single plasticizer physical blend into a stable network with durable flexibility and anti-aging ability, solving the problems of easy migration and precipitation of plasticizers and long-term storage performance degradation in existing starch films, and improving the mechanical durability and water-blocking stability of the film.

[0022] 2. In this invention, the modified chitosan-based reinforcing material is acylated with acetic anhydride to introduce hydrophobic ester groups to improve water resistance, crosslinked with epichlorohydrin to construct an internal bridging network to enhance mechanical strength, and then synergistically composited with nano-zinc oxide and polyethylene glycol. Polyethylene glycol acts as a dispersant, stabilizer, and flexible linker, enabling the nano-zinc oxide to achieve uniform nanoscale dispersion and long-term stability within the chitosan matrix. Simultaneously, the hydrophilic segments of polyethylene glycol endow the material with continuous protonation and water retention capacity in neutral and slightly acidic environments. This overcomes the limitation that chitosan only exerts antibacterial activity under acidic conditions, solving the problems of easy agglomeration of nanoparticles, decreased mechanical properties of composite materials, and pH-dependent antibacterial activity in existing technologies. This enhances the material's broad-spectrum, long-lasting antibacterial properties and mechanical reinforcement effect.

[0023] 3. In this invention, the modified nanocellulose-based hydrophobic material is stearate-esterified and grafted with long-chain hydrophobic alkyl groups to reduce surface energy. The esterification structure is stabilized by citric acid crosslinking and additional carboxyl groups are introduced. Then, after controlled hydrolysis of γ-glycidoxypropyltrimethoxysilane in an alcohol-water mixed solvent, it forms stable siloxane bonds with the hydroxyl groups on the surface of nanocellulose and covalently grafts them. At the same time, the epoxy active groups are retained as reaction sites for subsequent chemical crosslinking. The hydrophobic segments are firmly anchored to the surface of nanocellulose through chemical bonding and endowed with the ability to undergo covalent reactions with the matrix. This solves the problems of weak interfacial bonding and easy phase separation of composite films in the prior art due to surface adsorption or single esterification hydrophobic modification, and enhances the hydrophobicity and chemical reactivity of nanocellulose. Detailed Implementation

[0024] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0025] It should be noted that the raw materials used in the following embodiments are all commercially available.

[0026] Example 1: An edible nanocomposite coating material with a biomimetic plant cuticle structure, composed of the following raw materials in parts by weight: 100 parts modified starch-based film-forming material, 20 parts modified chitosan-based reinforcing material, and 6 parts modified nanocellulose-based hydrophobic material.

[0027] The modified starch-based film-forming material is prepared by treating starch with hydrogen peroxide, maleic anhydride, sodium trimetaphosphate, and sodium stearoyl lactylate.

[0028] The modified chitosan-based reinforced material is prepared by treating chitosan with acetic anhydride, epichlorohydrin, and nano-zinc oxide polyethylene glycol.

[0029] Modified nanocellulose-based hydrophobic materials are prepared by treating nanocellulose with stearic acid, citric acid, and γ-glycidoxypropyltrimethoxysilane.

[0030] The modified starch-based film-forming material is prepared as follows: starch is dissolved in deionized water to prepare a starch slurry with a mass fraction of 10%, hydrogen peroxide is added, and the mixture is stirred at 40°C for 1 hour to obtain oxidized starch; maleic anhydride is added to the oxidized starch, the pH is adjusted to 7.0, and the mixture is stirred at 50°C for 2 hours to obtain maleic anhydride esterified starch; sodium trimetaphosphate is added to the maleic anhydride esterified starch, the pH is adjusted to 9.0, and the mixture is stirred at 40°C for 1 hour to obtain crosslinked esterified oxidized starch; sodium stearoyl lactylate is added to the crosslinked esterified oxidized starch, and the mixture is stirred at 50°C for 1 hour to undergo composite plasticizing treatment, followed by filtration, washing, and drying to obtain the modified starch-based film-forming material.

[0031] The amount of hydrogen peroxide added was 3% of the dry weight of starch; the mass ratio of maleic anhydride to starch was 1:10; the mass ratio of sodium trimetaphosphate to starch was 1:30; and the mass ratio of sodium stearoyl lactylate to starch was 1:40.

[0032] The preparation method of modified chitosan-based reinforcing material is as follows: chitosan is dissolved in a 1% (w / w) aqueous acetic acid solution to prepare a 3% (w / w) chitosan solution. Acetic anhydride is added, and the mixture is stirred at 40°C for 2 hours to obtain esterified chitosan. Epichlorohydrin is added to the esterified chitosan, and the mixture is stirred at 50°C for 3 hours to obtain crosslinked esterified chitosan. Nano-zinc oxide is mixed with polyethylene glycol, dispersed in deionized water, ultrasonically dispersed for 20 minutes, and then added to the crosslinked esterified chitosan. The mixture is stirred and compounded at 40°C for 2 hours. After filtration, washing, and drying, the modified chitosan-based reinforcing material is obtained.

[0033] The mass ratio of acetic anhydride to chitosan is 1:4; the mass ratio of epichlorohydrin to chitosan is 1:6; nano zinc oxide and polyethylene glycol are mixed at a mass ratio of 1:2, with the amount of nano zinc oxide added being 4% of the mass of chitosan and the amount of polyethylene glycol added being 9% of the mass of chitosan.

[0034] The preparation method of modified nanocellulose-based hydrophobic material is as follows: nanocellulose is dispersed in deionized water to prepare a nanocellulose suspension with a mass fraction of 1%, stearic acid is added, and the mixture is stirred at 60℃ for 2 hours to obtain esterified nanocellulose; citric acid is added to the esterified nanocellulose, and the mixture is stirred at 70℃ for 1 hour to obtain crosslinked esterified nanocellulose; the crosslinked esterified nanocellulose is dispersed in an ethanol-water mixed solvent, γ-glycidoxypropyltrimethoxysilane is added, the pH is adjusted to 5.0, and the mixture is stirred at 50℃ for 1 hour to obtain a coupling reaction. After filtration, washing, and drying, the modified nanocellulose-based hydrophobic material is obtained.

[0035] The mass ratio of stearic acid to nanocellulose is 1:3; the mass ratio of citric acid to nanocellulose is 1:6; the volume ratio of ethanol to water in the ethanol-water mixed solvent is 1:5; and the mass ratio of γ-glycidyl etheroxypropyltrimethoxysilane to nanocellulose is 1:15.

[0036] A method for preparing an edible nanocomposite coating material with a biomimetic plant cuticle structure includes the following steps: S1. Dissolve the modified starch-based film-forming material in deionized water to prepare a film-forming solution with a mass fraction of 4%. Add a plasticizer and gelatinize at 70°C for 20 minutes. Cool down to 40°C, add the modified chitosan-based reinforcing material, and stir and mix for 30 minutes. This allows the polyethylene glycol segments on the modified chitosan-based reinforcing material and the sodium stearoyl lactylate on the modified starch-based film-forming material to form a physical cross-linked network through hydrogen bonds and hydrophobic interactions.

[0037] S2. Add modified nanocellulose-based hydrophobic material to the mixture obtained in S1. The epoxy groups of γ-glycidyl etheroxypropyltrimethoxysilane on the surface of the modified nanocellulose-based hydrophobic material undergo ring-opening addition reaction with the hydroxyl and amino groups on the modified chitosan-based reinforcing material and the modified starch-based film-forming material in the mixture in S1 to form chemical covalent crosslinks. Stir and disperse for 20 min to obtain composite film-forming liquid.

[0038] S3. Vacuum degas the composite film-forming liquid for 10 minutes, and then cast it onto a flat substrate, controlling the casting thickness to be 0.5 mm.

[0039] S4. The film cast in S3 is dried at 40°C for 6 hours to obtain an edible nanocomposite coating material with a biomimetic plant cuticle structure.

[0040] The plasticizer is glycerin, and the amount of glycerin added is 15-30% of the mass of the modified starch-based film-forming material.

[0041] Application of edible nanocomposite coating material with biomimetic plant cuticle structure: The edible nanocomposite coating material is prepared into a coating liquid with a mass fraction of 3%, sprayed onto the surface of fruits and vegetables, and dried with hot air at 30°C to form an edible nanocomposite coating with biomimetic plant cuticle structure on the surface of fruits and vegetables.

[0042] Example 2: An edible nanocomposite coating material with a biomimetic plant cuticle structure, composed of the following raw materials in parts by weight: 100 parts modified starch-based film-forming material, 20-30 parts modified chitosan-based reinforcing material, and 6-12 parts modified nanocellulose-based hydrophobic material.

[0043] The modified starch-based film-forming material is prepared by treating starch with hydrogen peroxide, maleic anhydride, sodium trimetaphosphate, and sodium stearoyl lactylate.

[0044] The modified chitosan-based reinforced material is prepared by treating chitosan with acetic anhydride, epichlorohydrin, and nano-zinc oxide polyethylene glycol.

[0045] Modified nanocellulose-based hydrophobic materials are prepared by treating nanocellulose with stearic acid, citric acid, and γ-glycidoxypropyltrimethoxysilane.

[0046] The modified starch-based film-forming material is prepared as follows: starch is dissolved in deionized water to prepare a starch slurry with a mass fraction of 15%, hydrogen peroxide is added, and the mixture is stirred at 50°C for 2 hours to obtain oxidized starch; maleic anhydride is added to the oxidized starch, the pH is adjusted to 7.5, and the mixture is stirred at 60°C for 3 hours to obtain maleic anhydride esterified starch; sodium trimetaphosphate is added to the maleic anhydride esterified starch, the pH is adjusted to 9.5, and the mixture is stirred at 50°C for 1.5 hours to obtain crosslinked esterified oxidized starch; sodium stearoyl lactylate is added to the crosslinked esterified oxidized starch, and the mixture is stirred at 55°C for 1.5 hours to undergo composite plasticizing treatment, followed by filtration, washing, and drying to obtain the modified starch-based film-forming material.

[0047] The amount of hydrogen peroxide added was 4% of the dry weight of starch; the mass ratio of maleic anhydride to starch was 1:15; the mass ratio of sodium trimetaphosphate to starch was 1:35; and the mass ratio of sodium stearoyl lactylate to starch was 1:45.

[0048] The preparation method of modified chitosan-based reinforcing material is as follows: chitosan is dissolved in a 1% (w / w) aqueous acetic acid solution to prepare a 4% (w / w) chitosan solution. Acetic anhydride is added, and the mixture is stirred at 50°C for 3 hours to obtain esterified chitosan. Epichlorohydrin is added to the esterified chitosan, and the mixture is stirred at 60°C for 4 hours to obtain crosslinked esterified chitosan. Nano-zinc oxide is mixed with polyethylene glycol, dispersed in deionized water, ultrasonically dispersed for 25 minutes, and then added to the crosslinked esterified chitosan. The mixture is stirred and compounded at 50°C for 2.5 hours. After filtration, washing, and drying, the modified chitosan-based reinforcing material is obtained.

[0049] The mass ratio of acetic anhydride to chitosan is 1:5; the mass ratio of epichlorohydrin to chitosan is 1:8; nano zinc oxide and polyethylene glycol are mixed at a mass ratio of 1:3, with the amount of nano zinc oxide added being 6% of the mass of chitosan and the amount of polyethylene glycol added being 10.5% of the mass of chitosan.

[0050] The modified nanocellulose-based hydrophobic material is prepared as follows: nanocellulose is dispersed in deionized water to prepare a nanocellulose suspension with a mass fraction of 2%, stearic acid is added, and the mixture is stirred at 70°C for 3 hours to obtain esterified nanocellulose; citric acid is added to the esterified nanocellulose, and the mixture is stirred at 90°C for 2 hours to obtain crosslinked esterified nanocellulose; the crosslinked esterified nanocellulose is dispersed in an ethanol-water mixed solvent, γ-glycidoxypropyltrimethoxysilane is added, the pH is adjusted to 5.7, and the mixture is stirred at 60°C for 1.5 hours to obtain a coupling reaction; the mixture is then filtered, washed, and dried to obtain the modified nanocellulose-based hydrophobic material.

[0051] The mass ratio of stearic acid to nanocellulose is 1:4; the mass ratio of citric acid to nanocellulose is 1:8; the volume ratio of ethanol to water in the ethanol-water mixed solvent is 1:7.5; and the mass ratio of γ-glycidoxypropyltrimethoxysilane to nanocellulose is 1:20.

[0052] A method for preparing an edible nanocomposite coating material with a biomimetic plant cuticle structure includes the following steps: S1. Dissolve the modified starch-based film-forming material in deionized water to prepare a film-forming solution with a mass fraction of 5%. Add a plasticizer and gelatinize at 80°C for 30 minutes. Cool down to 50°C, add the modified chitosan-based reinforcing material, and stir and mix for 45 minutes. This allows the polyethylene glycol segments on the modified chitosan-based reinforcing material and the sodium stearoyl lactylate on the modified starch-based film-forming material to form a physical cross-linked network through hydrogen bonds and hydrophobic interactions.

[0053] S2. Add modified nanocellulose-based hydrophobic material to the mixture obtained in S1. The epoxy groups of γ-glycidyl etheroxypropyltrimethoxysilane on the surface of the modified nanocellulose-based hydrophobic material undergo ring-opening addition reaction with the hydroxyl and amino groups on the modified chitosan-based reinforcing material and the modified starch-based film-forming material in the mixture in S1 to form chemical covalent crosslinks. Stir and disperse for 30 min to obtain composite film-forming liquid.

[0054] S3. Degas the composite film-forming liquid under vacuum for 15 minutes, and then cast it onto a flat substrate, controlling the casting thickness to be 1.2 mm.

[0055] S4. The film cast in S3 is dried at 50°C for 9 hours to obtain an edible nanocomposite coating material with a biomimetic plant cuticle structure.

[0056] The plasticizer is glycerol, and the amount of glycerol added is 22.5% of the mass of the modified starch-based film-forming material.

[0057] Application of edible nanocomposite coating material with biomimetic plant cuticle structure: The edible nanocomposite coating material is prepared into a coating liquid with a mass fraction of 4%, sprayed onto the surface of fruits and vegetables, and dried with hot air at 35°C to form an edible nanocomposite coating with biomimetic plant cuticle structure on the surface of fruits and vegetables.

[0058] Example 3: An edible nanocomposite coating material with a biomimetic plant cuticle structure, composed of the following raw materials in parts by weight: 100 parts modified starch-based film-forming material, 30 parts modified chitosan-based reinforcing material, and 12 parts modified nanocellulose-based hydrophobic material.

[0059] The modified starch-based film-forming material is prepared by treating starch with hydrogen peroxide, maleic anhydride, sodium trimetaphosphate, and sodium stearoyl lactylate.

[0060] The modified chitosan-based reinforced material is prepared by treating chitosan with acetic anhydride, epichlorohydrin, and nano-zinc oxide polyethylene glycol.

[0061] Modified nanocellulose-based hydrophobic materials are prepared by treating nanocellulose with stearic acid, citric acid, and γ-glycidoxypropyltrimethoxysilane.

[0062] The preparation method of the modified starch-based film-forming material is as follows: starch is dissolved in deionized water to prepare a starch slurry with a mass fraction of 20%, hydrogen peroxide is added, and the mixture is stirred at 60°C for 3 hours to obtain oxidized starch; maleic anhydride is added to the oxidized starch, the pH is adjusted to 8.0, and the mixture is stirred at 70°C for 4 hours to obtain maleic anhydride esterified starch; sodium trimetaphosphate is added to the maleic anhydride esterified starch, the pH is adjusted to 10.0, and the mixture is stirred at 60°C for 2 hours to obtain crosslinked esterified oxidized starch; sodium stearoyl lactylate is added to the crosslinked esterified oxidized starch, and the mixture is stirred at 60°C for 2 hours to undergo composite plasticizing treatment, followed by filtration, washing, and drying to obtain the modified starch-based film-forming material.

[0063] The amount of hydrogen peroxide added is 5% of the dry weight of starch; the mass ratio of maleic anhydride to starch is 1:20; the mass ratio of sodium trimetaphosphate to starch is 1:40; and the mass ratio of sodium stearoyl lactylate to starch is 1:50.

[0064] The preparation method of modified chitosan-based reinforcing material is as follows: chitosan is dissolved in a 1% (w / w) aqueous acetic acid solution to prepare a 5% (w / w) chitosan solution. Acetic anhydride is added, and the mixture is stirred at 60°C for 4 hours to obtain esterified chitosan. Epichlorohydrin is added to the esterified chitosan, and the mixture is stirred at 70°C for 5 hours to obtain crosslinked esterified chitosan. Nano-zinc oxide is mixed with polyethylene glycol, dispersed in deionized water, ultrasonically dispersed for 30 minutes, and then added to the crosslinked esterified chitosan. The mixture is stirred and compounded at 60°C for 3 hours. After filtration, washing, and drying, the modified chitosan-based reinforcing material is obtained.

[0065] The mass ratio of acetic anhydride to chitosan is 1:6; the mass ratio of epichlorohydrin to chitosan is 1:10; nano zinc oxide and polyethylene glycol are mixed at a mass ratio of 1:4, with the amount of nano zinc oxide added being 8% of the mass of chitosan and the amount of polyethylene glycol added being 12% of the mass of chitosan.

[0066] The preparation method of modified nanocellulose-based hydrophobic material is as follows: nanocellulose is dispersed in deionized water to prepare a nanocellulose suspension with a mass fraction of 3%, stearic acid is added, and the mixture is stirred at 80℃ for 4 hours to obtain esterified nanocellulose; citric acid is added to the esterified nanocellulose, and the mixture is stirred at 90℃ for 3 hours to obtain crosslinked esterified nanocellulose; the crosslinked esterified nanocellulose is dispersed in an ethanol-water mixed solvent, γ-glycidoxypropyltrimethoxysilane is added, the pH is adjusted to 6.5, and the mixture is stirred at 70℃ for 2 hours to obtain a coupling reaction. After filtration, washing, and drying, the modified nanocellulose-based hydrophobic material is obtained.

[0067] The mass ratio of stearic acid to nanocellulose is 1:5; the mass ratio of citric acid to nanocellulose is 1:10; the volume ratio of ethanol to water in the ethanol-water mixed solvent is 1:10; and the mass ratio of γ-glycidyl etheroxypropyltrimethoxysilane to nanocellulose is 1:25.

[0068] A method for preparing an edible nanocomposite coating material with a biomimetic plant cuticle structure includes the following steps: S1. Dissolve the modified starch-based film-forming material in deionized water to prepare a film-forming solution with a mass fraction of 6%. Add a plasticizer and gelatinize at 90°C for 40 min. Cool down to 60°C, add the modified chitosan-based reinforcing material, and stir and mix for 60 min. This allows the polyethylene glycol segments on the modified chitosan-based reinforcing material and the sodium stearoyl lactylate on the modified starch-based film-forming material to form a physical cross-linked network through hydrogen bonding and hydrophobic interactions.

[0069] S2. Add modified nanocellulose-based hydrophobic material to the mixture obtained in S1. The epoxy groups of γ-glycidyl etheroxypropyltrimethoxysilane on the surface of the modified nanocellulose-based hydrophobic material undergo ring-opening addition reaction with the hydroxyl and amino groups on the modified chitosan-based reinforcing material and the modified starch-based film-forming material in the mixture in S1 to form chemical covalent crosslinks. Stir and disperse for 40 min to obtain composite film-forming liquid.

[0070] S3. Vacuum degas the composite film-forming liquid for 20 minutes, and then cast it onto a flat substrate, controlling the casting thickness to be 2.0 mm.

[0071] S4. The film cast in S3 is dried at 60°C for 12 hours to obtain an edible nanocomposite coating material with a biomimetic plant cuticle structure.

[0072] The plasticizer is glycerin, and the amount of glycerin added is 30% of the mass of the modified starch-based film-forming material.

[0073] Application of edible nanocomposite coating material with biomimetic plant cuticle structure: The edible nanocomposite coating material is prepared into a coating liquid with a mass fraction of 5%, sprayed onto the surface of fruits and vegetables, and dried with hot air at 40℃, thus forming an edible nanocomposite coating with biomimetic plant cuticle structure on the surface of fruits and vegetables.

[0074] Comparative Example 1: The difference between this comparative example and Example 1 is that the modified starch-based film-forming material in this comparative example is replaced with untreated starch.

[0075] Comparative Example 2 differs from Example 1 in that the modified chitosan-based reinforcing material is replaced with untreated chitosan.

[0076] Comparative Example 3 differs from Example 1 in that the modified nanocellulose-based hydrophobic material in this comparative example is replaced with untreated nanocellulose.

[0077] Performance testing: The relevant properties of the edible nanocomposite coating materials with biomimetic plant cuticle structures provided in Examples 1 to 3 and Comparative Examples 1 to 3 were tested respectively, and the test data are recorded in Table 1 below: Table 1 - Performance Test Table of Edible Nanocomposite Coating Materials with Plant Cuticle Structure Among them, the plasticizer migration rate of the edible nanocomposite coating material with biomimetic plant cuticle structure prepared by Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2 and Comparative Example 3 in GB31604.30-2016 was tested.

[0078] The diameter of the antibacterial zone of the edible nanocomposite coating material with a biomimetic plant cuticle structure prepared according to the test methods in GB / T38483-2020 (Examples 1, 2, 3, Comparative Examples 1, 2, and 3) was tested.

[0079] The water vapor transmission rate of edible nanocomposite coating materials with biomimetic plant cuticle structure prepared according to the test methods in GB / T1037-2021 in Examples 1, 2, 3, Comparative Examples 1, 2, and 3 was tested.

[0080] By comparing and analyzing the relevant data in the table, it can be seen that the edible nanocomposite coating material with a biomimetic plant cuticle structure prepared by this invention has a low plasticizer migration rate, indicating that the plasticizer has good adhesion to the membrane matrix and is not easily migrated or lost during long-term storage; the large diameter of the antibacterial zone indicates that the material dissolves more antibacterial active ingredients and has a strong antibacterial effect; the low water vapor permeability indicates that the membrane material has strong hydrophobic barrier properties, which can effectively block the penetration of external moisture and the loss of internal moisture. Therefore, it is evident that the edible nanocomposite coating material with a biomimetic plant cuticle structure provided by this invention, along with its preparation method and application, has a broader market prospect and is more suitable for promotion.

[0081] In the description of this specification, references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.

[0082] The preferred embodiments of the present invention disclosed above are merely illustrative of the invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the invention to the specific implementations described. Clearly, many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize the invention. The invention is limited only by the claims and their full scope and equivalents.

Claims

1. An edible nanocomposite coating material with a biomimetic plant cuticle structure, characterized in that, It is composed of the following raw materials in parts by weight: 100 parts modified starch-based film-forming material, 20-30 parts modified chitosan-based reinforcing material, and 6-12 parts modified nanocellulose-based hydrophobic material; The modified starch-based film-forming material is prepared by treating starch with hydrogen peroxide, maleic anhydride, sodium trimetaphosphate, and sodium stearoyl lactylate. The modified chitosan-based reinforcing material is prepared by treating chitosan with acetic anhydride, epichlorohydrin, and nano-zinc oxide polyethylene glycol. The modified nanocellulose-based hydrophobic material is prepared by treating nanocellulose with stearic acid, citric acid, and γ-glycidoxypropyltrimethoxysilane.

2. The edible nanocomposite coating material with a biomimetic plant cuticle structure according to claim 1, characterized in that, The modified starch-based film-forming material is prepared as follows: starch is dissolved in deionized water to prepare a starch slurry with a mass fraction of 10-20%, hydrogen peroxide is added, and the mixture is stirred at 40-60℃ to oxidize the starch to obtain oxidized starch; maleic anhydride is added to the oxidized starch, the pH is adjusted to 7.0-8.0, and the mixture is stirred at 50-70℃ to undergo an esterification reaction to obtain maleic anhydride esterified starch; sodium trimetaphosphate is added to the maleic anhydride esterified starch, the pH is adjusted to 9.0-10.0, and the mixture is stirred at 40-60℃ to undergo a crosslinking reaction to obtain crosslinked esterified oxidized starch; sodium stearoyl lactylate is added to the crosslinked esterified oxidized starch, and the mixture is stirred at 50-60℃ for composite plasticizing treatment, followed by filtration, washing, and drying to obtain the modified starch-based film-forming material.

3. The edible nanocomposite coating material with a biomimetic plant cuticle structure according to claim 2, characterized in that: The amount of hydrogen peroxide added is 3-5% of the dry weight of starch; the mass ratio of maleic anhydride to starch is 1:10-20; the mass ratio of sodium trimetaphosphate to starch is 1:30-40; and the mass ratio of sodium stearoyl lactylate to starch is 1:40-50.

4. The edible nanocomposite coating material with a biomimetic plant cuticle structure according to claim 1, characterized in that, The preparation method of the modified chitosan-based reinforcing material is as follows: chitosan is dissolved in a 1% (w / w) aqueous acetic acid solution to prepare a 3-5% (w / w) chitosan solution; acetic anhydride is added, and the mixture is stirred at 40-60℃ to undergo an esterification reaction to obtain esterified chitosan; epichlorohydrin is added to the esterified chitosan, and the mixture is stirred at 50-70℃ to undergo a crosslinking reaction to obtain crosslinked esterified chitosan; nano zinc oxide is mixed with polyethylene glycol, dispersed in deionized water, ultrasonically dispersed, and then added to the crosslinked esterified chitosan; the mixture is stirred and compounded at 40-60℃, then filtered, washed, and dried to obtain the modified chitosan-based reinforcing material.

5. The edible nanocomposite coating material with a biomimetic plant cuticle structure according to claim 4, characterized in that: The mass ratio of acetic anhydride to chitosan is 1:4-6; the mass ratio of epichlorohydrin to chitosan is 1:6-10; the nano zinc oxide and polyethylene glycol are mixed at a mass ratio of 1:2-4, the amount of nano zinc oxide added is 4-8% of the mass of chitosan, and the amount of polyethylene glycol added is 9-12% of the mass of chitosan.

6. The edible nanocomposite coating material with a biomimetic plant cuticle structure according to claim 1, characterized in that, The modified nanocellulose-based hydrophobic material is prepared as follows: nanocellulose is dispersed in deionized water to prepare a nanocellulose suspension with a mass fraction of 1-3%, stearic acid is added, and esterification reaction is carried out at 60-80℃ to obtain esterified nanocellulose; citric acid is added to the esterified nanocellulose, and crosslinking reaction is carried out at 70-90℃ to obtain crosslinked esterified nanocellulose; the crosslinked esterified nanocellulose is dispersed in an ethanol-water mixed solvent, γ-glycidoxypropyltrimethoxysilane is added, the pH is adjusted to 5.0-6.5, and coupling reaction is carried out at 50-70℃. After filtration, washing, and drying, the modified nanocellulose-based hydrophobic material is obtained.

7. The edible nanocomposite coating material with a biomimetic plant cuticle structure according to claim 6, characterized in that: The mass ratio of stearic acid to nanocellulose is 1:3-5; the mass ratio of citric acid to nanocellulose is 1:6-10; the volume ratio of ethanol to water in the ethanol-water mixed solvent is 1:5-10; and the mass ratio of γ-glycidoxypropyltrimethoxysilane to nanocellulose is 1:15-25.

8. A method for preparing an edible nanocomposite coating material with a biomimetic plant cuticle structure, comprising the edible nanocomposite coating material with a biomimetic plant cuticle structure as described in any one of claims 1-7, characterized in that, Includes the following steps: S1. Dissolve the modified starch-based film-forming material in deionized water to prepare a film-forming solution with a mass fraction of 4-6%, add a plasticizer, and gelatinize at 70-90℃; cool down to 40-60℃, add the modified chitosan-based reinforcing material, and stir to mix. S2. Add modified nanocellulose-based hydrophobic material to the mixture obtained in S1, carry out ring-opening addition reaction to form chemical covalent crosslinking, and stir to disperse to obtain composite film-forming liquid; S3. Vacuum degas the composite film-forming solution for 10-20 minutes, then cast it onto a flat substrate, controlling the casting thickness to be 0.5-2.0 mm. S4. Dry the film cast in S3 at 40-60℃ to obtain an edible nanocomposite coating material with a biomimetic plant cuticle structure.

9. The method for preparing the edible nanocomposite coating material with a biomimetic plant cuticle structure according to claim 8, characterized in that: The plasticizer is glycerol, and the amount of glycerol added is 15-30% of the mass of the modified starch-based film-forming material.

10. The application of an edible nanocomposite coating material with a biomimetic plant cuticle structure, referring to the edible nanocomposite coating material with a biomimetic plant cuticle structure as described in any one of claims 1-7, characterized in that: Edible nanocomposite coating material is prepared into a coating liquid with a mass fraction of 3-5%, sprayed onto the surface of fruits and vegetables, and dried with hot air at 30-40℃ to form an edible nanocomposite coating with a biomimetic plant cuticle structure on the surface of fruits and vegetables.